WE TEACH SOCIAL MARKETING CREATIVELY: THE EXPERIENCE OF PARTICIPANTS OF THE «NORWEGIAN PROJECT» - Malynka, Dr Oksana; Tomlins , Dr Richard (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The essence of social marketing and the specificity of its teaching to the participants of the Project of Social Adaptation and Facilitation of Military Veterans (the so-called «Norwegian Project») are explained. Successful case studies of social marketing campaigns and why they work, including how they reflect the «4 P's» of social marketing are described.